O Texto no Contexto Escolar: Limites e Possibilidades para a Produção de Texto no Ensino Médio - Lima, Maria da Penha Brandim de (2007)
The present work is related to the field research of the reading, writing and teaching Portuguese language and has as objective to study the limits of the writing textual producing in the school context. It intends to suggest some didactic procedures related to producing dissertative texts, which could help teachers to improve their pedagogical practice. For in such a way, we carry through a research-pilot with six teachers and sixty pupils, in six secondary grade schools of the state public net, situated in the region of Jundiaí, São Paulo. These schools were chosen due their results of the SARESP, 2004 edition and we had as a objective to draw a now existing picture of the producing text classes. The dissertation is based upon of the Textual Linguistic Theory, specifically in the principles of textuality considered by Beaugrande and Dressler (1994) and Beaugrande (1997), as well as in the guidance of the National Curriculum Parameters, given our concern with a textual production guided by the sociointeracional conception of text. The results gotten in the research-pilot point out to the necessity of considering procedures that propitiate the production of texts in effective communication situations, taking in to sideration, among others factors, the objectives of the production and interlocutors, as well as the aspects of textual organization. Bearing in mind such results, we present, in the end of the work, some procedures of dissertative text production, that could be used by the teachers in classrooms of Portuguese language